The Influence of Leadership Style and Communication In Improving Employee Performance at Government Official Schools - Nurhedhi Desriyanto; Wahyu Kurniawan; Ichyu Machmiyana; Feti Fatonah; Dody Wahyu Widodo (Journal of Social Research, 2025)
This study aims to determine whether leadership and communication styles can improve employee performance in civil service schools. The performance of employees in organizations, particularly educational institutions, is influenced by factors such as effectiveness, efficiency, authority, responsibility, discipline, and initiative. The research adopts a literature study method, where secondary data from existing sources is analyzed to gain insights into the relationship between leadership styles, communication effectiveness, and employee performance. The findings indicate that leadership style plays a significant role in enhancing employee performance, with effective leadership fostering motivation, trust, and collaboration among staff. Furthermore, the study highlights that communication styles, particularly open and transparent communication, have a positive impact on employee performance by fostering clarity, reducing misunderstandings, and improving coordination within the organization. In conclusion, both leadership and communication styles are crucial factors in improving employee performance in civil service schools, suggesting that leadership development programs and communication training should be prioritized to optimize organizational effectiveness and productivity.